ASEAN migrant workers and its impacts on Malaysian society - Abdullah, Haslinda; Mohamed Shaffril, Hayrol Azril; Md. Yassin, Sulaiman (Institute of Islam Hadhari, Universiti Kebangsaan Malaysia; together with Faculty of Human Ecology, Universiti Putra Malaysia; and Department of Islamic Development Malaysia, 2015)
Malaysia aims to achieve the status of developed country by 2020. To realize this, each sector is accelerating their development progress, especially in the industrial, services and agriculture. To support this rapid development, problems related to inadequate number of human resources need to be solved and reliance on the migrant workers seem to be an effective solution. Although the migrant workers are providing strong support to the development progress in Malaysia, nevertheless, their presence in a big number are said to impact the local community. This paper aims to provide a conceptual understanding on the impacts of migrant workers on the Malaysian society. This paper relies on document analyses and reviews of literature as the main technique in collecting the required data. Based on the analyses performed, it can be concluded that albeit migrant workers huge contribution towards the country development especially in term of providing adequate number of human resources, their presence in a big number are found to results in several negative impacts in relation to the economics, social, health, safety and security aspects of the Malaysian community. Based on the findings, the paper highlights a number of recommendations and it is a hope that it can assist harmonise existence of the migrant workers in Malaysian community.